The Impact of Social Media on Organizational Performance: A Study of Airtel-tigo Ghana - Agonou, Elizabeth (UniMAC - GIJ, 2021)
This study is focused on investigating the impact of Social Media Usage on the organizational performance of AirtelTigo, Ghana. Using a quantitative research approach, data were collected from a total number of 122 staff of AirtelTigo using a questionnaire form to answer questions relating to the aspects of social media use in the organization, specifically social media for marketing, social media for customer relations and services and social media for information accessibility. Organizational performance was also measured in five factors comprising of rapid adaptation, time to market, cost reduction, satisfaction and innovation. From the findings, it was reported that social media use in AirtelTigo was largely for customer relations and services, followed by for marketing and then for information accessibility. For organizational performance, AirtelTigo largely considered the use of social media for satisfaction as the topmost followed by the time to market, to innovation, to rapid adaptation and then to cost reduction in that order. Again, the use of social media for marketing positively relatives to the time to market of new product offerings to the market, the use of social media for customer relations and services also relates positively to satisfaction of products and services and the use of social media for information accessibility also relating positively to innovation within the country. Overall, the use of social media significantly impacts on the organizational performance of AirtelTigo given the OLS regression results. It is therefore recommended that the telecommunication industry engage more of their social media platforms as it has significant impacts its organizational performance. AirtelTigo must also invest in a workforce with the knowledge of social media platforms so they can harness the opportunities it brings to the organization.
THESIS